Gossip on the Doxiadis ‘Gossip Square’: Unpacking the Histories of an Unglamorous Public Space - Panayiota Pyla (Architectural Histories, 2013)
Understanding the historical complexities surrounding Doxiadis Associates’ idea of ‘gossip squares’ in housing projects helps frame larger theoretical questions about the potential significance of the ‘gossip square’ as an everyday public space. The focus of this paper is the gossip square as a spatial and social concept. The idea of 'gossip square' was discussed among Doxiadis Associates' designers and patrons, to eventually become entwined with larger visions of urban development. In examining the ‘gossip square’, new ‘gossip’ arises about how the term reflected ambivalent alignments with mid-twentieth-century modernism, and how it advanced particular agendas of nation-building and modernization. Unpacking the history of the term and the way the concept was appropriated (or not) by the firm of Doxiadis Associates provides insights into such public hubs in the larger context of social relations and the space of a city.